Disentangling the Relationship Between Social Protection and Social Cohesion: Introduction to the Special Issue - Francesco Burchi; Markus Loewe; Daniele Malerba; Julia Leininger (The European Journal of Development Research, 2022)
While there is substantial evidence of the effect of social protection on poverty and vulnerability, limited research has focused on societal outcomes. This paper serves as introduction to a special issue (SI) examining the relationship between social protection and social cohesion in low- and middle-income countries. Over the last years, social cohesion has emerged as a central goal of development policy. The introduction and the papers in the SI use a common definition of social cohesion as a multi-faceted phenomenon, comprising three attributes: cooperation, trust and inclusive identity. This introductory article provides a conceptual framework linking social protection to social cohesion, shows the current empirical evidence for the bi-directional linkages, and highlights how the papers in the SI contribute to filling existing research gaps. In addition to this introduction, the SI encompasses seven papers, covering different world regions and social protection schemes, and using different quantitative and qualitative methods.
Keywords: D63; H41; H53; H55; I38; 330; Social protection; Social cohesion; Cash transfers; Public works; Graduation programmes; Empirical evidence; Mixed methods